2005
DOI: 10.1016/j.ijhcs.2005.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The mechanics of trust: A framework for research and design

Abstract: With an increasing number of technologies supporting transactions over distance and replacing traditional forms of interaction, designing for trust has become a core concern for researchers in both HCI and CMC. While much research focuses on increasing trust in mediated interactions, this paper takes a systemic view to identify the factors that support trustworthy behavior. In a second step, we analyze how the presence of these factors can be signaled to allow the formation of well-placed trust. For our analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
308
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(316 citation statements)
references
References 67 publications
(53 reference statements)
7
308
0
1
Order By: Relevance
“…While the emergence of the Internet and e-commerce is a quite recent phenomenon, the research on trust spans a wide area of further disciplines such as sociology, psychology or economics (Riegelsberger et al 2005). Consequently, there are just as many definitions and researchers even disagree on basic characteristics (McKnight and Chervany 1996;Gefen et al 2003).…”
Section: Online Trust and Reputation Systemsmentioning
confidence: 99%
“…While the emergence of the Internet and e-commerce is a quite recent phenomenon, the research on trust spans a wide area of further disciplines such as sociology, psychology or economics (Riegelsberger et al 2005). Consequently, there are just as many definitions and researchers even disagree on basic characteristics (McKnight and Chervany 1996;Gefen et al 2003).…”
Section: Online Trust and Reputation Systemsmentioning
confidence: 99%
“…In terms of e--commerce, and with particular reference to online gambling, it is widely recognised that customer service in terms of meeting customer needs and alleviating difficulties (Phillips et al, 2013) and subsequent trustworthiness (Riegelsberger et al, 2005;Wood & Griffiths, 2008) increase the likelihood of a customer using that company (Lee et al, 2014). Research has previously demonstrated that customers perceive online gambling operators' attempts to reduce player gambling--related harm positively, and beyond more favourable attitudes can lead to an increase in desire and intention to gamble with that operator (Song et al, 2012;Wood & Griffiths, 2008).…”
Section: Player Usage Of Responsible Gambling Featuresmentioning
confidence: 99%
“…We refer to the extant literature, see for example [13] and [4], for a more thorough discussion of trust mechanisms and their role in general system design. Empirical work done by social scientists in the general space of trust perceptions and its support in decision making is an important source of information for the design of user-facing trust aggregation languages.…”
Section: Related Workmentioning
confidence: 99%